2018
DOI: 10.1089/end.2018.0086
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Radical Prostatectomy in Patients with High-Risk Prostate Cancer: Feasibility and Safety. Results of a Multicentric Study

Abstract: According to our encouraging data about oncological and functional outcomes we believe that radical prostatectomy represents an effective treatment for patients with high-risk PCa and that laparoscopy is a safe approach offering a mini-invasive alternative to open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 26 publications
3
8
1
Order By: Relevance
“…Similarly the distribution of biopsy GS was variable. A score below 8 in more than half of the cases was reported by few authors [11,14,16,18,19]; while a score of 8 or more was noted by others, including us [5,10,17]. However, patient's clinical stage in our study was similar to the other reports.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similarly the distribution of biopsy GS was variable. A score below 8 in more than half of the cases was reported by few authors [11,14,16,18,19]; while a score of 8 or more was noted by others, including us [5,10,17]. However, patient's clinical stage in our study was similar to the other reports.…”
Section: Discussionsupporting
confidence: 84%
“…PSA distribution among the various other studies of HRPC treatment by RP was not uniform ( Table 5). Mean PSA around 10ng/ml was found in a few studies [7,10,14,15,16,17] while a value between 15-25ng/ml was observed in others, including in our study [5,11,18,19]. Similarly the distribution of biopsy GS was variable.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Because of the familiar route and reliable touch [ 12 ], ORP has always been the “gold standard” treatment for PCa [ 13 ], but since 1991, LRP for PCa treatment has been widely disseminated in an attempt to decrease morbidity compared with the traditional ORP [ 14 ], even though with high-risk PCa patients [ 15 ]. With the improvement of the modern technology and the advent of robotic instruments, RARP was promptly applied in the USA and some developed European countries as the most common extirpative treatment for PCa [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the familiar route and reliable touch [12] , ORP has always been the "gold standard" treatment for PCa [13] but since 1991, LRP for PCa treatment has been widely disseminated in an attempt to decrease morbidity compared with the traditional ORP [14] , even though with high-risk PCa patients [15] . With the improvement of the modern technology and the advent of robotic instruments, RARP was promptly applied in the United States and some developed European countries as the most common extirpative treatment for PCa [16] .…”
Section: Discussionmentioning
confidence: 99%